Relationship between Circulating Tumor Cells, Blood Coagulation, and Urokinase‐Plasminogen‐Activator System in Early Breast Cancer Patients. Issue 2 (27th January 2015) - Mego, Michal; Karaba, Marian; Minarik, Gabriel; Benca, Juraj; Sedlácková, Tatiana; Tothova, Lubomira; Vlkova, Barbora; Cierna, Zuzana; Janega, Pavol; Luha, Jan; Gronesova, Paulina; Pindak, Daniel; et al.
Abstract Cancer is a risk factor for venous thromboembolism (VTE) and plasma d‐dimer (DD) and tissue factor (TF) are established VTE associated markers. Circulating tumor cells (CTCs) are associated with the risk of VTE in metastatic breast cancer. This study aimed to correlate CTCs, blood coagulation and the urokinase plasminogen activator (uPA) system in primary breast cancer (PBC) patients. This prospective study included 116 PBC patients treated by primary surgery. CTCs were detected by quantitative RT‐PCR assay for expression of epithelial (CK19) or epithelial‐mesenchymal transition (EMT) genes (TWIST1, SNAIL1, SLUG, ZEB1, FOXC2). Plasma DD, TF, uPA system proteins were detected by enzyme‐linked immunosorbent assays, while expressions of uPA system in surgical specimens were evaluated by immunohistochemistry. CTCs were detected in 27.6% patients. Patients with CTCs had a significantly higher mean plasma DD (ng/mL) than those of patients without CTCs (632.4 versus 365.4, p = 0.000004). There was no association between plasma TF and CTCs. Epithelial CTCs exhibit higher expression of uPA system genes compared to EMT_CTCs. Patients with CTCs had higher plasma uPA proteins than those of patients without CTCs; there was no correlation between tissue expression of uPA system, CTCs, DD or TF levels. In multivariate analysis CTCs and patients age were independent factors associated with plasma DD. We found association between plasma DD and CTCs indicating a potential role for activation of the coagulation cascade in the early metastatic process. CTCs could be directly involved in coagulation activation or increased CTCs could be marker of aggressive disease and increased VTE risk.